Penggunaan Sistem Informasi Akuntansi pada Usaha Kecil dan Menengah (UKM) di Provinsi Riau - Ulfa Afifah; Ruhul Fitrios; Mayla Khoiriyah (Jurnal Akuntansi Keuangan dan Bisnis, 2022)
The purpose of this study was to test the effect of the use of accounting information systems on individual performance on Small and Medium Enterprises (SMEs) in Riau Province, Indonesia. This is due to the low use of information systems in small and medium-sized businesses. The study was conducted on 258 SMEs in Riau Province. The study used descriptive methods and tested the results using the Partial Least Square-Structural Equation Model (PLS-SEM). The results of this study state that management's commitment has an influence on the use of accounting information systems and the use of accounting information systems affects individual performance. Through verification, it was concluded that to increase the use of SME accounting information systems can be done through strengthening management commitments so as to improve individual performance. The originality of this research is a theoretical construction built to solve the problem of SMEs, besides that there is rarely research conducted related to SIA in SMEs in Riau Province. Therefore, SME management is expected to understand that Accounting Information Systems are the main proponents of their business activities, then use them to achieve the performance of individual employees and organizations.